Experimental analysis of overcharged Li-polymer batteries. (September 2020) - Ciorba, Serena; Marracci, Mirko; Antonetti, Claudia; Martinelli, Marco; Caposciutti, Gianluca; Tellini, Bernardo; Raspolli Galletti, Anna Maria
Abstract: Since safety hazards can occur during the life of a Li-ion battery, understanding its behavior under abusive conditions is important for the development of a safe cell. In this work, overcharge tests on commercial Li-polymer cells were conducted in a climatic chamber, resulting in gas evolution. A comprehensive post-mortem analysis of the abused cells was carried out: the exhaust gases were identified by gas phase chromatography coupled with a thermal conductivity detector (micro-GC/TCD), then flammable and toxic species were detected; the cathode and anode materials were analyzed using scanning electron microscopy (SEM) and energy dispersive X-ray spectrometry (EDS), while the electrolyte composition was studied by Fourier-transform infrared spectroscopy (FT-IR). Interestingly, the ambient temperature seemed to affect the degradation of the cell materials and hence the composition of the evolved gas. Graphical abstract: Image 1